PESAN POLITIK PADA DEKLARASI #2019GANTIPRESIDEN Analisis Wacana pada detik.com Periode 4 Mei s.d. 4 Juni 2018 - Suprassetyo, Teguh; Darmawan, Arif; Ayodya, Beta Puspitaning (Universitas 17 Agustus 1945 Surabaya, 2019)
Ahead of the 2019 election there were a number of movements, one of which was the declaration of #2019GantiPresiden. This movement became pro and contra and became a popular conversation between the general public and the political elite which was considered to contain political content. The mass media was also crowded in announcing the declaration of movement #2019GantiPresiden, one of them is online mass media Detik.com. For this reason researchers are interested in conducting research on the political message of the declaration #2019GantiPresiden in the online mass media news detik.com. The research was conducted using discourse analysis of Teun A. Van Dijk and then related to propaganda techniques. The results of the research conducted indicate that the political message in declaration #2019GantiPresiden in detik.com news period May 4 to June 4 2018 contains a propaganda political message that uses repetition propaganda techniques, namely the repeated presentation of messages so that people are easily remembered.Keywords : political message, discourse analysis, #2019GantiPresiden, propaganda technique